Aging and well-being in Goa, India: a qualitative study. (1st February 2018) - Cohen, Alex; Dias, Amit; Azariah, Fredric; Krishna, Revathi N.; Sequeira, Miriam; Abraham, Sherin; Cuijpers, Pim; Morse, Jennifer Q.; Reynolds, Charles F.; Patel, Vikram
ABSTRACT: Objectives: The population of India is aging rapidly. This demographic shift brings with it a host of challenges to the health and well-being of older adults, including the increased prevalence of non-communicable diseases, among them depressive disorders. In this paper, we report on qualitative research intended to inform the development of a locally acceptable and appropriate intervention to improve the well-being of older adults in Goa, India and, specifically, to prevent late-life depression. Method: Semi-structured interviews with 20 individuals, aged 60 years and older, attending two primary care clinics in Goa, India. Transcripts were reviewed to identify emerging themes, a coding scheme was developed and thematic analyses were conducted. Results: Analyses of the interview transcripts revealed the following key themes: (1) notions of old age tended to be negative and there were widespread fears of becoming widowed or incapacitated; (2) the most frequently reported health conditions were joint pain, diabetes and heart disease; (3) emotional distress was described using the terms 'tension', 'stress', 'worry' and 'thinking'; (4) family issues often involved financial matters, difficult relationships with daughters-in-law and conflicted feelings about living with the family or independently; (5) other than a pension scheme, participants did not know of community resources available to older adults. Conclusions: Our findings are in general agreement with those of previous research, and with our experiences of working with older adults in Pittsburgh and the Netherlands. This research will inform the development of an intervention to prevent depression in older adults in Goa.